Associations between life-course-persistent antisocial behaviour and brain structure in a population-representative longitudinal birth cohort. (March 2020) - Carlisi, Christina O; Moffitt, Terrie E; Knodt, Annchen R; Harrington, Honalee; Ireland, David; Melzer, Tracy R; Poulton, Richie; Ramrakha, Sandhya; Caspi, Avshalom; Hariri, Ahmad R; Viding, Essi
Summary: Background: Studies with behavioural and neuropsychological tests have supported the developmental taxonomy theory of antisocial behaviour, which specifies abnormal brain development as a fundamental aspect of life-course-persistent antisocial behaviour, but no study has characterised features of brain structure associated with life-course-persistent versus adolescence-limited trajectories, as defined by prospective data. We aimed to determine whether life-course-persistent antisocial behaviour is associated with neurocognitive abnormalities by testing the hypothesis that it is also associated with brain structure abnormalities. Methods: We used structural MRI data collected at 45 years of age from participants in the Dunedin Study, a population-representative longitudinal birth cohort of 1037 individuals born between April 1, 1972, and March 31, 1973, in Dunedin, New Zealand, who were resident in the province and who participated in the first assessment at 3 years of age. Participants underwent MRI, and mean global cortical surface area and cortical thickness were extracted for each participant. Participants had been previously subtyped as exhibiting life-course-persistent, adolescence-limited, or no history of persistent antisocial behaviour (ie, a low trajectory group) based on informant-reported and self-reported conduct problems from the ages of 7 years to 26 years. Study personnel who processed the MRI images were masked to antisocial group membership. We used linear estimated ordinary least squares regressions to compare each antisocial trajectory group (life-course persistent and adolescence limited) with the low trajectory group to examine whether antisocial behaviour was related to abnormalities in mean global surface area and mean cortical thickness. Next, we used parcel-wise linear regressions to identify antisocial trajectory group differences in surface area and cortical thickness. All results were controlled for sex and false discovery rate corrected. Findings: Data from 672 participants were analysed, and 80 (12%) were classified as having life-course-persistent antisocial behaviour, 151 (23%) as having adolescence-limited antisocial behaviour, and 441 (66%) as having low antisocial behaviour. Individuals on the life-course-persistent trajectory had a smaller mean surface area (standardised β=–0·18 [95% CI −0·24 to −0·11]; p<0·0001) and lower mean cortical thickness (standardised β=–0·10 [95% CI −0·19 to −0·02]; p=0·020) than did those in the low group. Compared with the low group, the life-course-persistent group had reduced surface area in 282 of 360 anatomically defined parcels and thinner cortex in 11 of 360 parcels encompassing circumscribed frontal and temporal regions associated with executive function, affect regulation, and motivation. Widespread differences in brain surface morphometry were not observed for the adolescence-limited group compared with either non-antisocial behaviour or life-course-persistent groups. Interpretation: These analyses provide initial evidence that differences in brain surface morphometry are associated with life-course-persistent, but not adolescence-limited, antisocial behaviour. As such, the analyses are consistent with the developmental taxonomy theory of antisocial behaviour and highlight the importance of using prospective longitudinal data to define different patterns of antisocial behaviour development. Funding: US National Institute on Aging, Health Research Council of New Zealand, New Zealand Ministry of Business, Innovation and Employment, UK Medical Research Council, Avielle Foundation, and Wellcome Trust.